Study on the structural differences between Heidaigou long flame coal and its vitrinite. Issue 1 (2nd January 2019) - Lian, Jun; Lin, Hualin; Xue, Yuan; Sheng, Han
ABSTRACT: Heidaigou long flame coal (HDC), with high inertinite content but outstanding liquefaction properties and its vitrinite (HDV) were studied. The structural characteristics of HDC and HDV were studied simultaneously on the basis of structure models developed by 13 C cross-polarization/magic angle spinning nuclear magnetic resonance (NMR) and X-ray photoelectron spectroscopy (XPS). Aliphatic structures, aromatic structures, and the structures of nitrogen and oxygen in HDC and HDV were investigated and compared. Besides, the different structures and units in HDC and HDV were found and represented.